The Impact of Angle Tilted Glass Panels on Solar Energy Gained in Different Buildings Function - Rawa; Yunis (Iraqi Journal of Architecture and Planning, 2012)
Tilted of glass panels of windows is one of the solutions to reduce the solar energy gain depending on the angle of solar radiation and transmittance of glass panel. The variance of hour's usage of the different functional spaces (residential, administrative, and educational), requires different treatment due to the different amount of energy gain. This determined the research problem as: the absence of a clear vision about tilted of windows glass panels and its impact on solar energy for different buildings.The research aim is to determine the appropriate tilted of glass panels of windows according to the period of occupations to help the architect for approval in his designs within the city of Baghdad The research identified equations resulting from the geometrical analysis of the relationship between the direction of solar radiation and the tilted of glass window, using (Microsoft Office Excel program) to measure varies window's glass panels ranged between (0Â° to 30Â°) towards the inside or outside the space in different geographical directions, and calculate the amount of seasonal gained energy (summer and winter) up to the annual efficiency of the thermal performance.The research obtain number of diagrams (as protractors according to the function of space), could help the architect to determine the most efficient angle for tilted glass window depending on the direction and type of glass used, these protractors can be adopted in windows design of Baghdad city.